Numerical modelling of thermal distribution control in a furnace (2018)
Application of control to heat treatment processes helps to achieve the desired mechanical properties of materials but improper controller design is a major problem causing short lifespan of components of locally made furnaces. In this study, the numerical control of the temperature distribution within a furnace cavity was carried out using COMSOL Multiphysics and Simulink. Six sensor points within the furnace cavity (with and without specimen) were selected and each point was consecutively used to observe the time response of the sensor to the desired temperature. The results from the time response analysis indicated uneven temperature distribution within the furnace with points located at the corners of the furnace recording the highest temperature rise while points at the centre of the furnace or within the specimen having the lowest temperature. Thus, the best position for a sensor is at any corner of the furnace to protect the components of the furnace from damage.